A possible new conceptual basis in biophysics - Svetla E Teodorova (Journal of Biology and Medicine - Peertechz Publications, 2019)
For the time being, the biological processes are described based on theoretical apparatus of thermodynamics, mechanics, dynamic systems theory etc. Here a new conceptual basis for description of living objects in their entirety and overall response is suggested. Biology and medicine gain if the organism physiological status could be assessed via prompt and simple measurements. New variables as vitality, biological energy, and synergy are introduced as integral phenomenological characteristics of biological objects. Sinergy is presumed to be a measure of biological selfregulation quality. Biological principle for maximum synergy in undisturbed state is postulated. An equation describing the recovery process of an organism after some disturbance is obtained. The synergy change in possible outcomes after different influences is discussed. The new approach, new variables and laws could form a new science field. This paper could stimulate the scientific thought for further research.